2020
DOI: 10.1659/mrd-journal-d-19-00069.1
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Current and Future Distribution of the Invasive Weed Ageratina adenophora in the Chitwan–Annapurna Landscape, Nepal

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…The spatiotemporal distribution pattern of A. adenophora is shaped by the interaction between biological characteristics and multiple environmental variables, such as temperature and precipitation. Previous studies have identified the minimum temperature of the coldest month (Bio6) as a significant variable determining the geographical distribution of A. adenophora in Nepal (Poudel et al, 2020). Consistently, our results showed that the geographic distribution of A. adenophora in China is shaped by the combination of precipitation and temperature variables.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The spatiotemporal distribution pattern of A. adenophora is shaped by the interaction between biological characteristics and multiple environmental variables, such as temperature and precipitation. Previous studies have identified the minimum temperature of the coldest month (Bio6) as a significant variable determining the geographical distribution of A. adenophora in Nepal (Poudel et al, 2020). Consistently, our results showed that the geographic distribution of A. adenophora in China is shaped by the combination of precipitation and temperature variables.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the geographical distribution of A. adenophora may expand to Southeast China, which has suitable climatic conditions for colonization. To date, regional studies in Nepal (Poudel et al, 2020), India (Chaudhary et al, 2021), and South Africa (Tererai & Wood, 2014) have predicted that the geographic distribution of A. adenophora will expand under climate change. Therefore, climate warming appears to be conducive to the survival of A. adenophora , augmenting its global invasion risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that the winter temperature and minimum temperature of the coldest month have a significant impact on the distribution of A. adenophora in China and Nepal (Poudel et al, 2020;Fang et al, 2021). In general, A. adenophora prefers to grow in warm temperature conditions, such as between 10-25 • C (Sun et al, 2004;Tererai and Wood, 2014).…”
Section: Significant Environmental Variablesmentioning
confidence: 99%
“…The total suitable habitat areas of A. adenophora will increase under RCP 8.5 in the 2070s compared with that under the current climate. Some studies have indicated that the PGD of A. adenophora will expand by 45.3% and 2% under RCP 8.5 in India and Nepal, respectively (Poudel et al, 2020;Chaudhary et al, 2021). Our findings were consistent with this pattern.…”
Section: The Changes In the Distribution Pattern Of A Adenophora Unde...mentioning
confidence: 99%